AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN DAN AMPAS TEH HIJAU (Camellia sinensis L. ) TERHADAP BAKTERI PENYEBAB JERAWAT (Propionibacterium acne DAN Staphylococcus epidermidis ) SECARA DIFUSI AGAR - Herwin Herwin; Zulhisda Premeita Sari; Siska Nuryanti (Fakultas Farmasi UMI, 2018)
Acne is one skin problem commonly known as acne vulgaris, that is a state where the skin pores are clogged. Some of the bakteria causing the growth on acne are Propianibacterium acne and Staphylococcus epidermidis . Green tea (Camellia sinensis L.) is one of the plants that can be useful as antibacterial. This study aimed to obtained the antibacterial activity of ethanol extract leaves and sregs of green tea which has the potential to inhibit the growth of acne causing bacteria by the agar diffusion method. The simplisia of green tea leaves and dregs are macerated with ethanol 96% and obtained the weight of ethanol extract of green tea leaves 34.6 grams. In determination of Minimum Inhibitory Concentration (MIC) ethanol extract of the leaves and the dregs, the MIC value obtained is the same as the two test bacteria on the concentration of 0.1%; whereas, KBM value is on the concentration of 0.4%. The result of the antibacterial activity of ethanol extract of green tea leaves at the largest concentration of 8% has an inhibitory zone diameter of 18.11 mm to Propianibacterium acne and 18.05 mm to Staphylococcus epidermidis. For the antibacterial activity test of ethanol extract the green tea dregs at the largest concentration of 8% has the largest average inhibitory zone diameter of 17.45 mm against Propinibacterium acne and 15.68 mm against Staphylococcus epidermidis.